Towards a City Region? Determining How the Inter-Municipal Cooperation on Commercial Land Development in the Region Halle/Leipzig can be Classified as a Form of Regional Governance - Pyschny, Andreas; Wilde, Erik; Knippschild, Robert (Raumforschung und Raumordnung | Spatial Research and Planning, 2012)
An inter-municipal and informal cooperation dealing with commercial land development exists in the region Halle/Leipzig since 2009. The cooperation is formed by cities and villages and extends over the border between the two federal states of Saxony and Saxony-Anhalt. The article gives an overview of the previous steps and its main results, i.e. conclusions of an evaluation of the commercial land potential in the region Halle/Leipzig. In addition, it describes the functioning as well as the communication patterns within the cooperation. However, the main goal of this article is to determine how the inter-municipal cooperation can be classified as a form of regional governance, based on the theoretical debate on that topic. General conclusions will be drawn as well as implications for the upcoming process in the region Halle/Leipzig.